2004
DOI: 10.1177/004051750407400102
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility of Cotton Blend Perpendicular-Laid Nonwovens

Abstract: Perpendicular-laid and cross-laid highloft nonwoven fabrics are constructed of cotton, polyester, and bicomponent co-polyester bonding fibers. Kawabata parameters describing the compressional resistance and recovery of these fabrics are measured with a comput erized Q-test instrument. Results are obtained from tests replicated by two independent operators in triplicate and on different dates. Compared to cross-laid fabrics, perpendic ular-laid fabrics show higher compressional resistance and superior elastic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…After passing through the chamber the vertically lapped fabric is cooled and wound up (4). In addition a supporting layer (5) can be brought from below onto the conveyor belt of the bonding chamber to produce two-layer nonwoven fabric [10].…”
Section: Fiber Materials and Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…After passing through the chamber the vertically lapped fabric is cooled and wound up (4). In addition a supporting layer (5) can be brought from below onto the conveyor belt of the bonding chamber to produce two-layer nonwoven fabric [10].…”
Section: Fiber Materials and Processesmentioning
confidence: 99%
“…In this technology, fibers are processed into vertically lapped highloft nonwovens. Struto technology consists of carding, vertical layering of the carded webs, and thermal bonding using[10]. The fabric samples listed inTable IIwere produced by Struto International Inc. Kings Mountain, NC [11].…”
mentioning
confidence: 99%
“…Kucuk M and Korkmaz Y measured sound absorption properties of eight different nonwoven composites including different fiber types mixed with different ratios, they stated that the increase in thickness and the decrease in air permeability results in an increase in sound absorption properties of the material [8]. Perpendicular-laid nonwovens exhibit excellent compression recovery, softness and very good sound absorption performance since perpendicular-laid nonwovens have highloft structure where all the fibers are orientated in the vertical plane [9,10,11]. Tascan and Vaughn investigated the acoustical insulation of perpendicular-laid nonwoven fabrics made from different polyester fibers, and stated that fabrics made from 3 denier fibers have better sound insulation than those made from 15 denier fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic, mechanical, and thermal properties of perpendicular-laid nonwovens have been studied by researchers. 310 Tascan and colleagues 34 investigated the effect of fiber geometry and fabric density on acoustic behavior of perpendicular-laid nonwoven fabrics. They stated that fabrics made from 3 denier fibers are better sound absorbers and insulators than those made from 15 denier fibers; their results indicated that the perpendicular-laid nonwoven fabrics made from 4DG and trilobal fibers show better sound insulation results than nonwoven fabrics made from round fibers.…”
mentioning
confidence: 99%
“…The compressional behavior of perpendicular-laid nonwovens was introduced by Parikh and colleagues. [9][10] They compared the compressional resistance of perpendicular-laid and cross-laid nonwovens, and concluded that perpendicular-laid nonwovens have higher compressional resistance and better recovery properties than cross-laid nonwovens.…”
mentioning
confidence: 99%